2022
DOI: 10.3390/plants11020162
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulants in Viticulture: A Sustainable Approach against Biotic and Abiotic Stresses

Abstract: Climate change and disproportionate anthropogenic interventions, such as the excess of phytopharmaceutical products and continuous soil tillage, are jeopardizing viticulture by subjecting plants to continuous abiotic stress. One of the main physiological repercussions of abiotic stress is represented by the unbalanced redox homeostasis due to the overproduction of reactive oxygen species (ROS), ultimately leading to a state of oxidative stress (detrimental to grape quality). To these are added the direct and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 213 publications
0
26
0
Order By: Relevance
“…According to eco-friendly approaches and increasing organic wine demands, the global scientific community focused on developing alternatives to Cu in order to reduce and/or replace it in main crops, such as grapevine. There are many substances under ongoing testing and validation and some are already on the global market, such as inorganic substances (i.e., zeolite, potassium and sodium hydrogen carbonate); biological control agents (BCAs); biostimulants, including also arbuscular mycorrhizal fungi (AMF) and plant growth-promoting rhizobacteria (PGPR), and resistance inducer (RI) products [11,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to eco-friendly approaches and increasing organic wine demands, the global scientific community focused on developing alternatives to Cu in order to reduce and/or replace it in main crops, such as grapevine. There are many substances under ongoing testing and validation and some are already on the global market, such as inorganic substances (i.e., zeolite, potassium and sodium hydrogen carbonate); biological control agents (BCAs); biostimulants, including also arbuscular mycorrhizal fungi (AMF) and plant growth-promoting rhizobacteria (PGPR), and resistance inducer (RI) products [11,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Several bioformulates based on Trichoderma spp., Streptomyces spp., Aureobasidium pullulans, Bacillus subtilis and B. amyloliquefaciens are used to manage gray mold infections, whereas Ampelomyces quisqualis-based formulates are applied for the control of the powdery mildew of grape [1,17]. With regard to biostimulants, the most promising and widely used are seaweed extracts, protein hydrolysates, humic and fulvic acids, silicon, AMF and PGPR [18]. Several studies showed that mycorrhizal colonization provides pathogen protection through inducing plant systemic resistance [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The standard viticultural practices adopted by the farm were applied in all the vineyards, including cluster thinning (to 1.5 bunch/shoot), leaf thinning (4 interventions), mineral nutrition (fertilizer units: 135 N, 57 P 2 O 5 , 115 K 2 O, 80 CaO, 25 MgO) provided partly by soil distribution and partly by fertigation, and irrigation provided by sub-surface system (2000 m 3 /year as total amount of annual delivered water). Biostimulants were also applied to counteract biotic and abiotic stresses [35]. Grapes under covers were harvested in the last ten days of July; harvest in open field started 15 days later.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several eco-friendly tools and approaches have been proposed and implemented to improve production in terms of agricultural sustainability [ 7 , 8 , 9 ]. One approach has been to provide naturally derived compositions and safe inputs, known as biostimulants, to treat crop plants.…”
Section: Introductionmentioning
confidence: 99%